2019
DOI: 10.1021/acs.jproteome.9b00003
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Roles of N-Glycans on Collagen–Platelet Interactions

Abstract: Collagen is a potent agonist for platelet activation, presenting itself as a key contributor to coagulation via interactions with platelet glycoproteins. The fine details dictating platelet−collagen interactions are poorly understood. In particular, glycosylation could be a key determinant in the platelet−collagen interaction. Here, we report an affinity purification coupled to a mass spectrometry-based approach to elucidate the function of N-glycans in dictating platelet−collagen interactions. By integrative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Another study detected 0.8 k extra-cytosolic N-linked glycosylation sites with some of these regulated by GPVI [63]. This agrees with the finding that glycan glycosylation plays a role in plateletcollagen interaction [64]. In GPVI-stimulated platelets, it appeared that 0.9 k out of 1.6 k ubiquitinylated peptides (corresponding to 0.7 k proteins, including Syk, filamin and integrins) were upregulated, implicating a profound role of GPVI in the ubiquitin protein degradation pathway [65].…”
Section: Collagen Receptor Glycoprotein VI (Gpvi)supporting
confidence: 82%
“…Another study detected 0.8 k extra-cytosolic N-linked glycosylation sites with some of these regulated by GPVI [63]. This agrees with the finding that glycan glycosylation plays a role in plateletcollagen interaction [64]. In GPVI-stimulated platelets, it appeared that 0.9 k out of 1.6 k ubiquitinylated peptides (corresponding to 0.7 k proteins, including Syk, filamin and integrins) were upregulated, implicating a profound role of GPVI in the ubiquitin protein degradation pathway [65].…”
Section: Collagen Receptor Glycoprotein VI (Gpvi)supporting
confidence: 82%
“…Further supporting our results, the treatment of platelets with neuraminidase reduced their aggregation induced by ADP [ 27 ]. Moreover, abnormalities in the N-glycosylation of GPVI could contribute to acquired defects in GPVI-mediated platelet reactivity to collagen [ 8 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The function of platelet receptors that mediate their adhesive and aggregative properties are strongly reliant upon N-glycosylation to modulate the orientation of glycoproteins to facilitate interaction between proteins [ 29 ]. A mutational study performed on β3 demonstrated that loss of N-glycoside sites impaired either αIIbβ3 expression or function.…”
Section: Discussionmentioning
confidence: 99%
“…Under the high shear conditions, the GPIb-V-IX receptor complex is required to stabilize platelet adhesion to the vessel surface, besides collagen receptor glycoprotein (GP) VI and αIIbβ3 integrin, which indirectly interact with collagen via VWF [ 16 ]. Recent proteomics studies describe both the positive and negative influences of N-glycosylation on collagen-platelets interactions [ 17 ]. At low shear conditions, the binding to collagen via α2β1 integrin has a major role in platelet adhesion to the injured endothelium.…”
Section: Platelets Biology and Functionsmentioning
confidence: 99%